The Role of Couples’ Interacting World Assumptions and Relationship Adjustment in Women’s Postdisaster PTSD Symptoms - Monson, Candice M. (2009)
This study examined 58 heterosexual couples’ interacting assumptions about the world and relationship adjustment in predicting wives’ posttraumatic stress disorder (PTSD) symptoms after severe flooding. Both partners completed the World Assumptions Scale (Janoff-Bulman, 1989), and wives reported on their intimate relationship adjustment and PTSD symptomatology. Neither husbands’ nor wives’ assumptions alone predicted wives’ PTSD symptoms. However, the interaction of husbands’ and wives’ benevolent world assumptions significantly predicted wives’ PTSD symptoms. When husbands held less benevolent world assumptions, there was a negative association between wives’ assumptions and PTSD symptoms. Additionally, wives’ relationship adjustment predicted their PTSD symptomatology when taking into account individual and interacting self-worth assumptions. Implications for understanding the role of intimate relationships in postdisaster mental health and interpersonally oriented prevention efforts are discussed.